Biopsy outperforms reflectance confocal microscopy in diagnosing and subtyping basal cell carcinoma: results and experiences from a randomized controlled multicentre trial. (1st April 2021) - Woliner–van der Weg, W.; Peppelman, M.; Elshot, Y.S.; Visch, M.B.; Crijns, M.B.; Alkemade, H.A.C.; Bronkhorst, E.M.; Adang, E.; Amir, A.; Gerritsen, M.J.P.; van Erp, P.E.J.; Lubeek, S.F.K.
Summary: Background: Reflectance confocal microscopy (RCM) is a noninvasive method for skin assessment, allowing entire lesion evaluation up to the papillary dermis. RCM is a potentially attractive alternative to punch biopsy (PB) in basal cell carcinoma (BCC). Objectives: To determine the diagnostic accuracy of RCM vs. PB in diagnosing and subtyping BCC, and to study patient satisfaction and preferences. Methods: Patients with a clinically suspected primary BCC were randomized between RCM and biopsy. Conventional surgical excision or follow‐up were used as reference. Sensitivity and specificity for BCC diagnosis and subtyping were calculated for both methods. BCC subtype was stratified based on clinical relevance: aggressive (infiltrative/micronodular) vs. nonaggressive (superficial/nodular) histopathological subtype and superficial vs. nonsuperficial BCC. Data on patient satisfaction and preferences were collected using a questionnaire and a contingent valuation method. Results: Sensitivity for BCC diagnosis was high and similar for both methods (RCM 99·0% vs. biopsy 99·0%; P = 1·0). Specificity for BCC diagnosis was lower for RCM (59·1% vs. 100·0%; P < 0·001). Sensitivity for aggressive BCC subtypes was lower for RCM (33·3% vs. 77·3%; P = 0·003). Sensitivity for nonsuperficial BCC was not significantly different (RCM 88·9% vs. biopsy 91·0%; P = 0·724). Patient satisfaction and preferences were good and highly comparable for both methods. Conclusions: Biopsy outperforms RCM in diagnosing and subtyping clinically suspected primary BCC. This outcome does not support routine clinical implementation of RCM, as a replacement for PBs in this patient group.